A Role for Zinc in Plant Defense Against Pathogens and Herbivores - Cabot, Catalina; Martos, Soledad; Llugany, Mercè; Gallego, Berta; Tolrà, Roser; Poschenrieder, Charlotte (Frontiers in Plant Science, 2019)
Pests and diseases pose a threat to food security, which is nowadays aggravated by climate change and globalization. In this context, agricultural policies demand innovative approaches to more effectively manage resources and overcome the ecological issues raised by intensive farming. Optimization of plant mineral nutrition is a sustainable approach to ameliorate crop health and yield. Zinc is a micronutrient essential for all living organisms with a key role in growth, development and defense. Competition for Zn affects the outcome of the host-attacker interaction in both plant and animal systems. In this review we provide a clear framework of the different strategies involving low and high Zn concentrations launched by plants to fight their enemies. After briefly introducing the most relevant macro and micronutrients for plant defense, the functions of Zn in plant protection are summarized with especial emphasis on superoxide dismutases (SODs) and zinc finger proteins. Following, we cover recent meaningful studies identifying Zn-related passive and active mechanisms for plant protection. Finally, Zn-based strategies evolved by pathogens and pests to counteract plant defenses are discussed.